Bebarongan Creative Music “Hyang Surya” | Tabuh Kreasi Bebarongan “Hyang Surya” - Saputra, Putu Surya Aditya (GHURNITA: Jurnal Seni Karawitan, 2024)
Hyang Surya's Bebarongan percussion creation is to realize the artist's imagination regarding lighting every day on this Earth as a motivation to help achieve a new creative musical work. The light atmosphere from morning to evening is realized through the creative Bebarongan percussion using the gamelan Gong Kebyar. Natural lighting uses light from natural lights such as the sun, moon, and stars. Natural light is erratic, depending on climate, season, and weather. Natural lighting on Earth is illuminated by the sun; the Earth's sun rises in the morning, afternoon, and evening. Hyang Surya is another word for the sun god. Dewa or Hyang are holy creatures, supernatural beings, residents of heaven, angels, and manifestations of Brahman, namely (God Almighty). Surya is the name of the sun god according to Hindu belief. Sunlight reaches this Earth from morning, noon, until evening. Sunlight lighting is often liked and sought after by domestic and foreign tourist guests, such as in the morning when the sun rises and in the afternoon when the sun sets. Solar lighting also benefits living creatures like humans, animals, and plants.